Efficacy of electrical cranial stimulation for treatment of psychiatric symptoms in patients with anxiety: A systematic review and meta-analysis - Chung, Feng-Chin; Sun, Cheuk-Kwan; Chen, Yi; Cheng, Yu-Shian; Chung, Weilun; Tzang, Ruu-Fen; Chiu, Hsien-Jane; Wang, Ming-Yu; Cheng, Ying-Chih; Hung, Kuo-Chuan (Frontiers in Psychiatry, 2023)
Background: Therapeutic effects of electrical cranial stimulation (CES) in patients suffering from anxiety remained unclear. This meta-analysis aimed at investigating acceptability and therapeutic efficacy of CES against anxiety, depression, and insomnia for patients who experienced symptoms of anxiety. Methods: Major electronic databases were searched from inception until December 10, 2022 for randomized controlled trials (RCT) focusing on therapeutic effectiveness of CES in patients whose primary complaints included anxiety. Effect sizes (ES) for different treatment outcomes were estimated by using generic inverse variance method. Results: Eight RCTs were identified including a total of 337 participants. The therapeutic effectiveness of CES was significantly better than that in the control groups for anxiety (ES=-0.96, p<0.00001, eight trials, 337 patients), depression (ES=-0.69, p=0.003, five trials), and insomnia (ES=-1.02, p=0.0006, three trials) in those who presented with symptoms of anxiety. Subgroup analyses found that CES was equally effective regardless of comorbid presentation of depressive symptoms (ES=-0.94 in patients with anxiety only versus ES=-1.06 in those with depression and anxiety) and whether CES was used as monotherapy or add-on therapy to medications (ES=-0.88 vs. ES=-1.12, respectively). Moreover, subgroup analysis of RCTs using the same device “Alpha-Stim” for CES was more effective in alleviating anxiety than sham controls (ES=-0.88, p<0.00001, four trials, 230 patients). Regarding acceptability, the use of CES did not increase the risk of treatment-related dropout compared to the control group (RR=1.26, p=0.57, I2=0%, four trials, 324 patients). Conclusion: Our study supported the use of CES for symptoms of anxiety, depression, and insomnia in those suffering from anxiety with fair acceptability and demonstrated the efficacy of “Alpha-Stim”, the most commonly used device for CES, in this patient population.